Deficiency of pseudogene UPAT leads to hepatocellular carcinoma progression and forms a positive feedback loop with ZEB1. Issue 11 (6th September 2020) - Xiang, Leyang; Huang, Xiaoting; Wang, Siqi; Ou, Huohui; Chen, Zhanjun; Hu, Zhigang; Huang, Yu; Li, Xianghong; Yuan, Yawei; Yang, Dinghua
Abstract: Hepatocellular carcinoma (HCC) is a common disease worldwide. Accumulating reports have evidenced the internal connection between epithelial‐mesenchymal transition (EMT) and cancer stem cells (CSCs), as well as their significance in metastasis and post–operative recurrence. In this study, we investigated an interesting ubiquitin‐proteasome pathway associated pseudogene of AOC4, also known as UPAT, and showed that it was downregulated in 39.78% (37/93) of patients with hepatitis B virus (HBV)‐related HCC. Downregulation of UPAT was associated with multiple worse clinicopathological parameters, as well as decreased recurrence‐free survival (RFS). In vitro and in vivo assays found that overexpression of UPAT significantly suppressed cellular migration, invasion, EMT processes, and CSC properties. Mechanistic studies showed that UPAT promoted ZEB1 degradation via a ubiquitin‐proteasome pathway and, in contrast, ZEB1 transcriptionally suppressed UPAT by binding to multiple E‐box (CACCTG) elements in the promoter region. Moreover, UPAT was negatively correlated with ZEB1 protein in HCC tissues, their combined expression discriminated RFS outcomes for patients with HBV‐related HCC. These data on the UPAT‐ZEB1 circuit‐mediated pathway will further knowledge on EMT and CSCs, and may help to develop novel therapeutic approaches for the prevention of HCC metastasis. Abstract : We investigated a tumor suppressor pseudogene, UPAT, that was transcriptionally suppressed by ZEB1 in HCC. UPAT deficiency impaired ubiquitin‐proteasome pathway‐related ZEB1 degradation. By forming a UPAT/ZEB1 positive feedback loop, HCC cells were able to maintain EMT and CSC properties.